2015
DOI: 10.1155/2015/961208
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Internalized Silica Nanoparticles via STED Microscopy

Abstract: The development of safe engineered nanoparticles (NPs) requires a detailed understanding of their interaction mechanisms on a cellular level. Therefore, quantification of NP internalization is crucial to predict the potential impact of intracellular NP doses, providing essential information for risk assessment as well as for drug delivery applications. In this study, the internalization of 25 nm and 85 nm silica nanoparticles (SNPs) in alveolar type II cells (A549) was quantified by application of super-resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…STED was first used to study nanoparticle-cell interactions to demonstrate the nuclear localization and clustering of 30 nm fluorescent silica nanoparticles (SNPs) in Caco-2 cells 115,116 . More recently, Peuschel et al used 3D STED to quantify the internalization of 25 nm and 85 nm SNPs in A549 cells 117 and differentiate between membraneattached and internalized nanoparticles. A similar approach was also used to study the internalization and colocalization of carbon dots 118 and protein-based fluorescent nanoparticles 119 .…”
Section: [H2] Cellular Trafficking and Localizationmentioning
confidence: 99%
“…STED was first used to study nanoparticle-cell interactions to demonstrate the nuclear localization and clustering of 30 nm fluorescent silica nanoparticles (SNPs) in Caco-2 cells 115,116 . More recently, Peuschel et al used 3D STED to quantify the internalization of 25 nm and 85 nm SNPs in A549 cells 117 and differentiate between membraneattached and internalized nanoparticles. A similar approach was also used to study the internalization and colocalization of carbon dots 118 and protein-based fluorescent nanoparticles 119 .…”
Section: [H2] Cellular Trafficking and Localizationmentioning
confidence: 99%
“…73 Furthermore, the protein corona, consisting of proteins adsorbed at the NP surface, influences NP internalization and cytotoxicity. 71 The SiO 2 NPs used in this study did not affect the viability of HepG2 spheroids ( Figure 4). Also Dubiak-Szepietowska et al reported no cytotoxicity of SiO 2 NPs in HepG2 spheroids after 24 hours exposure.…”
Section: Cytotoxicity Of Sio 2 Nps In 3d Liver Microtissuesmentioning
confidence: 70%
“…70 In contrast, Schübbe et al and Peuschel et al described that SiO 2 NPs, which were prepared by the same synthesis, cause neither damage of membrane integrity, reduction of metabolic activity nor DNA damage in A549 and Caco-2 cells. 71,72 The contradictory results are due to differences in particle properties, cell type, and experimental conditions. SiO 2 NPs that have been prepared by different synthesis methods vary in their shape, size, and porosity which might cause different biological effects.…”
Section: Cytotoxicity Of Sio 2 Nps In 3d Liver Microtissuesmentioning
confidence: 99%
“…The physico-chemical features of the nanoparticles are the determining factors for the nanoparticle-living cell interactions and consequently influence cell behaviour. The size and shape of the nanomaterials and chemical functionalities on the surface play a critical role in binding the nanomaterials to cell membrane and subsequent cellular uptake [4][5][6]. This motivates pursuing research towards the biological interference of nanoparticles and development of multi-model diagnostic probes that could facilitate the combination dignostics, preferably covering both the anatomical and physiological aspect of various disease [7-8] including the deadly cancer.…”
Section: Introductionmentioning
confidence: 99%